The Influence Of Onboarding Training Program, Organisational Formal Control, Organisational Commitment And Transactional Leadership As A Moderator On Deviant Workplace Behaviour Among Federal Polytechnics Academicians In Nigeria - Ibrahim, Umar Sarkin Gardi (2024)
Nowadays, deviant workplace behaviour has become a primary financial and socio-economic concern for private and governmental organisations worldwide. Numerous works of Nigerian literature, national and international dailies, and media have reported staggering cases of organisational deviance with its attendant consequences. The most worrying of these cases is its prevalence among academics in the Nigerian high institution of learning. Works of literature have linked several factors with the problem. However, scholars have paid less attention to the employee’s early work experience, commitment to work and formal control. With the support of the Social Exchange Theory (SET) and Deterrence Theory (DT), this study examined the role of leadership style in moderating the effects of onboarding training, organisational control, and organisational commitment on deviant workplace behaviour. A quota sampling technique was applied to determine the research population.